Effects on intestinal microbiota and immune genes of Solea senegalensis after suspension of the administration of Shewanella putrefaciens Pdp11. (November 2016) - Vidal, Sara; Tapia-Paniagua, Silvana Teresa; Moriñigo, Jesús Miguel; Lobo, Carmen; García de la Banda, Inés; Balebona, María del Carmen; Moriñigo, Miguel Ángel
Abstract: The interaction host-intestinal microbiota is essential for the immunological homeostasis of the host. Probiotics, prebiotics and synbiotics are promising tools for the manipulation of the intestinal microbiota towards beneficial effects to the host. The objective of this study was to evaluate the modulation effect on the intestinal microbiota and the transcription of genes involved in the immune response in head kidney of Solea senegalensis after administration of diet supplemented with the prebiotic alginate and the probiotic Shewanella putrefaciens Pdp11 CECT 7627 (SpPdp11). The results showed higher adaptability to dietary changes in the intestinal microbiota of fish fed diet with alginate and SpPdp11 together compared to those fish that received an alginate-supplemented diet. The alginate-supplemented diet produced up-regulation of genes encoding proteins involved in immunological responses, such as complement, lysozyme G and transferrin, and oxidative stress, such as NADPH oxidase and glutation peroxidase. On the other hand, the administration of alginate combined with SpPdp11 resulted in a significant increase of the transcription of genes encoding for glutation peroxidase and HSP70, indicating a potential protective effect of SpPdp11 against oxidative stress. In addition, these effects were maintained after the suspension of the probiotic treatment. The relationship between the modulation of the intestinal microbiota and the expression of genes with protective effect against the oxidative stress was demonstrated by the Principal Components Analysis. Highlights: Alginate + SpPdp11 diet showed higher adaptation to dietary changes in the gut microbiota. Alginate + SpPdp11 increased the transcription of genes related to oxidative stress. Alginate-supplemented diet up-regulated genes involved in innate immunological response.